Financial Technology Regulation in Malaysia and Indonesia: A Comparative Study - Aulia Arifatu Diniyya; Mahdiah Aulia; Rofiul Wahyudi (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2021)
Introduction to The Problem: The era of innovation in information technology has emerged to ease daily commercial transactions. The innovation in financial technology has created numerous new business model to cater the customers’ need. This development needs a regulation and supervision to avoid chaos in the financial system. Particularly in Indonesia and Malaysia, which both countries were recorded by CCAF to be among the top countries in the ASEAN region by the number of fintech firms.Purpose/Objective Study: This study is aimed to analyze the financial technology regulation and supervision in Indonesia and Malaysia.Design/Methodology/Approach: The comparative study is conducted to compare the regulatory environment related to Digital payment, Equity Crowdfunding, P2P lending, Crypto Asset, Consumer protection, cybersecurity law and Islamic fintech in both countriesFindings: The study found that compared to Malaysia, Indonesia has lack of jurisdiction that protecting the customer from the cyber-attack which highly threatening the fintech industry. Both countries also treat ICO differently. Malaysia treats it under RMO guidelines, while Indonesia banned it as the method of payment but still allows the trading of ICO as a commodity under Commodity Futures Regulatory Agency.